2011
DOI: 10.1002/casp.1084
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational practice in the community: A focused ethnographic evaluation

Abstract: An intergenerational community intervention based on contact theory and using 'photovoice' methods was designed to change negative age-group stereotypes and promote sense of community. A focused ethnographic approach was adopted. Participants were 18 young people and 13 older adults. Data from focus groups, carried out with each generation separately, and observational field notes were analysed using thematic analysis; credibility checks were carried out by auditing and respondent validation. Before the interg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 32 publications
1
35
0
1
Order By: Relevance
“…According to Sanchez et al (2009), negative age stereotype influence one"s perception and his involvement in society as well as physical activity. Alcock et al (2011) also confirmed that negative stereotype caused the elderly being marginalized in society and social exclusion. As Hurlock (2009) and Erikson (1968) stated that social environment influences developmental task attainment, thus, the perception of ageism experienced by elderly in this study is aimed to represent the social challenge faced by elderly.…”
Section: Introductionsupporting
confidence: 54%
“…According to Sanchez et al (2009), negative age stereotype influence one"s perception and his involvement in society as well as physical activity. Alcock et al (2011) also confirmed that negative stereotype caused the elderly being marginalized in society and social exclusion. As Hurlock (2009) and Erikson (1968) stated that social environment influences developmental task attainment, thus, the perception of ageism experienced by elderly in this study is aimed to represent the social challenge faced by elderly.…”
Section: Introductionsupporting
confidence: 54%
“…(MacKenzie et al, 2010, p. iii) As interactionists have pointed out: 'cooperative action is possible as long as we know what one another is doing and we are able to communicate what we are doing and interpret what others are doing' (Charon, 2007, p. 158) -understanding one another's actions is essential. In practice this requires greater interaction between generations, such as community-level mediation and 'intergenerational programming (IP)', which have been shown to improve understanding and positive perceptions of one another (Alcock et al, 2011). This, in turn, can promote 'social capital', defined as:…”
Section: Resultsmentioning
confidence: 98%
“…The area fell within the 14% most deprived similar‐sized areas in England (Office for National Statistics, 2007). The last author (CH) was initially a volunteer on an intergenerational project (Alcock, Camic, Barker, Haridi, & Raven, ) and later employed by the youth centre on the estate. The service was funded via grants from charitable foundations.…”
Section: Methodsmentioning
confidence: 99%